UMKM DEVELOPMENT PROGRAM AND COMMUNITY EMPOWERMENT ON INCREASING PUBLIC INCOME - Hendra Hendra (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
This study examines best practice implementing the MSME Development Program and community empowerment on Increasing Community Budgeting using quantitative. This article investigating the big influence of the MSME development program on Increasing Community Income by alayzing how big is the Community Strengthening Against Community Revenue and how big is the influence of the UMKM Development Program and Community Empowerment together on Increasing Community Income in merangin district, Jambi, Indonesia. This paper employs descriptive analysis reviews that are supported by qualitative data to answer various problems of MSME development programs and community empowerment. Keywords: MSMEs, Empowerment, Community Income